Transcriptional Repression of CYP3A4 by Increased miR-200a-3p and miR-150-5p Promotes Steatosis in vitro - Huang, Zhijun; Wang, Mengyao; Liu, Li; Peng, Jinfu; Guo, Chengxian; Chen, Xiaoping; Huang, Lu; Tan, Jieqiong; Yang, Guoping (Frontiers in Genetics, 2019)
Hepatic cytochrome P450 enzyme activities correlate with non-alcoholic fatty liver disease (NAFLD) and hepatic steatosis. The decreased activity of CYP3A4, an important drug-metabolizing enzyme, is associated with the progression of NAFLD. CYP3A4 is predicted as a target gene of miR-200a-3p and miR-150-5p by MicroInspector and TargetScan algorithms analysis. Here, we found decreased CYP3A4 and increased miR-200a-3p and miR-150-5p in LO2 cells with free fatty acid (FFA)-induced steatosis. Dual-luciferase assay confirmed that both miR-200a-3p and miR-150-5p targeted 3′-untranslated region (3’-UTR) of CYP3A4, and that such interaction was abolished by miRNA binding site mutations in 3’-UTR of CYP3A4. Using miR-200a-3p and miR-150-5p mimics and inhibitors, we further confirmed that endogenous CYP3A4 was regulated post-transcriptionally by miR-200a-3p or miR-150-5p. Moreover, miR-200a-3p and miR-150-5p inhibitors attenuated FFA-induced steatosis in LO2 cells and such effect was dependent on CYP3Y4 expression. These results suggest that miR-200a-3p and miR-150-5p, through directly targeting 3′-UTR of CYP3A4, contribute to the development of FFA-induced steatosis.